Pengaruh Indeks Produksi Industri, BI Rate, dan Dana Pihak Ketiga Terhadap Penyaluran Kredit Perbankan di Indonesia Tahun 2016-2024 - Ira Amelia; Harya Kuncara Wiralaga; Karuniana Dianta A.S (Indo Publishing, 2026)
This study aims to analyze the effect of the Industrial Production Index (IPI), BI Rate, and Third-Party Funds (DPK) on bank credit distribution in Indonesia. This research employs a quantitative approach using the Autoregressive Distributed Lag (ARDL) method. The data used are monthly secondary data from 2016 to 2024 obtained from Bank Indonesia, the Financial Services Authority (OJK), the Central Bureau of Statistics (BPS), and CEIC Data. The ARDL method is applied to examine both short-run and long-run relationships among variables. The results show that in the long run, the Industrial Production Index (IPI) has a positive and significant effect on bank credit distribution, while the BI Rate and Third-Party Funds (DPK) do not have a significant effect. In the short run, Third-Party Funds (DPK) significantly affect credit distribution, whereas the Industrial Production Index (IPI) and BI Rate are not significant. These findings indicate that in the long term, credit distribution is driven more by real sector demand, while in the short term it is influenced by banking liquidity conditions. This study is expected to contribute to the development of economic knowledge, particularly in banking and monetary policy, and to serve as a reference for policymakers and banking institutions in formulating strategies to enhance sustainable credit distribution.